Clinical experience with pirfenidone in five patients with scleroderma-related interstitial lung disease - Miura, Yukiko; Saito, Takefumi; Fujita, Kazutaka; Tanaka, Toru; Tsunoda, Yoshiya; Azuma, Arata; Nei, Takahito; Yatagai, Yohei; Rin, Shigen; Sekine, Akimasa; Hayashihara, Kenji (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Interstitial lung disease is the most common complication and cause of death among patients with scleroderma. Scleroderma-related interstitial lung disease has usually been treated with cyclophosphamide; however, its effect was evaluated to be modest and long-term administration of this drug is associated with adverse effects. Herein, we report our clinical experience of administering pirfenidone, which is an antifibrotic agent, in five patients with scleroderma-related interstitial lung disease. All patients demonstrated an increase in vital capacity.